A Composite Contract for Coordinating a Supply Chain with Price and Effort Dependent Stochastic Demand. (3rd July 2016) - Liu, Yu-Shuang; Shang, Yun; Su, Hong-yan
Abstract : As the demand is more sensitive to price and sales effort, this paper investigates the issue of channel coordination for a supply chain with one manufacturer and one retailer facing price and effort dependent stochastic demand. A composite contract based on the quantity-restricted returns and target sales rebate can achieve coordination in this setting. Two main problems are addressed: (1 ) how to coordinate the decentralized supply chain; (2 ) how to determine the optimal sales effort level, pricing, and inventory decisions under the additive demand case. Numerical examples are presented to verify the effectiveness of combined contract in supply chain coordination and highlight model sensitivities to parametric changes.